Quantitative Proteomics Identifies Metabolic Pathways Affected by Babesia Infection and Blood Feeding in the Sialoproteome of the Vector Rhipicephalus bursa - Couto, Joana (2020)
The negative impact of ticks and tick-borne diseases on animals and human health is driving research to discover novel targets affecting both vectors and pathogens. The salivary glands are involved in feeding and pathogen transmission, thus are considered as a compelling target to focus research. In this study, proteomics approach was used to characterize Rhipicephalusbursa sialoproteome in response to Babesiaovis infection and blood feeding. Two potential tick protective antigens were identified and its influence in tick biological parameters and pathogen infection was evaluated. Results demonstrate that the R. bursa sialoproteome is highly affected by feeding but infection is well tolerated by tick cells. The combination of both stimuli shifts the previous scenario and a more evident pathogen manipulation can be suggested. Knockdown of ub2n led to a significative increase of infection in tick salivary glands but a brusque decrease in the progeny, revealing its importance in the cellular response to pathogen infection, which is worth pursuing in future studies. Additionally, an impact in the recovery rate of adults (62%), the egg production efficiency (45.75%), and the hatching rate (88.57 %) was detected. Building knowledge on vector and/or pathogen interplay bridges the identification of protective antigens and the development of novel control strategies.